Kontribusi Aisyah binti Abu Bakar dalam Tradisi Tafsir: Analisis Riwayat dalam Tafsir Ibn Kathir - Al Fahrizal; Umiatu Rohmah; Zia Ul Haramein; Khofawati Khoiriyyah; Sari Ratna Dewi (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study aims to examine the contribution of Aisyah binti Abu Bakar to the tradition of Qur’anic interpretation, particularly in relation to Surah an-Nisa’. This topic is important to demonstrate that women have played a significant role in the formation of Islamic intellectual traditions since the early period of Islam. This research employs a qualitative approach using a library research method by examining exegetical narrations attributed to Aisyah in Tafsir Ibn Kathir by Ibn Kathir. The data were collected through documentation techniques and analyzed using descriptive-analytical methods to identify the forms of Aisyah’s contributions in interpreting the verses of Surah an-Nisa’. The findings reveal that Aisyah made a significant contribution to the interpretation of Surah an-Nisa’. The narrations attributed to her demonstrate several important roles, including as a transmitter of exegetical narrations, as a source of information regarding the circumstances of revelation (asbāb al-nuzūl), and as an authoritative reference in understanding legal and social issues related to the verses of the surah. These findings indicate that women’s scholarly authority has been present in the tradition of Qur’anic exegesis since the early Islamic period and has contributed to enriching the intellectual heritage of Qur’anic interpretation. Therefore, this study highlights the importance of women’s roles in the historical development of tafsir and opens opportunities for further research on the contributions of female companions in Islamic scholarly traditions.